2005
DOI: 10.1111/j.1447-0756.2005.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological responses of progestin therapy for non‐atypical endometrial hyperplasia: A prospective study

Abstract: The current regimens of progestin therapy for non-atypical endometrial hyperplasia have high response rates. Patients who fail to have a clinical response should be evaluated for associated pelvic pathology. Follow-up endometrial biopsy should be offered to the patients, because 7.5% have persistent or progressive lesions, necessitating aggressive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Therefore, progesterone-based oral contraceptives are used for inhibition of endometrial hyperproliferation and improvement of menstrual dysfunction 25. In fact, approximately 92.5% of PCOS women who do not develop atypical endometrial hyperplasia after treatment have a return to normal endometria 26. Furthermore, treatment with megestrol progesterone or medroxyprogesterone can also improve certain cases of endometrial atypical hyperplasia in some PCOS women 27.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, progesterone-based oral contraceptives are used for inhibition of endometrial hyperproliferation and improvement of menstrual dysfunction 25. In fact, approximately 92.5% of PCOS women who do not develop atypical endometrial hyperplasia after treatment have a return to normal endometria 26. Furthermore, treatment with megestrol progesterone or medroxyprogesterone can also improve certain cases of endometrial atypical hyperplasia in some PCOS women 27.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up endometrial biopsy should be offered to the patients, because 7.5% have persistent or progressive lesions, necessitating aggressive treatment (14). In our study, the most commonly seen pelvic pathologies were not found to be associated with disease persistence.…”
Section: Discussionmentioning
confidence: 48%
“…15,16 For this reason, we further studied some of the possible molecular pathways involved in the mechanism of action of genistein aglycone in promoting the reduction of endometrial hyperplasia in subjects without signs of atypia. Growth factors involved in the establishment of endometrial hyperplasia act through kinase-associated receptors, and stimulate tissue and vascular growth.…”
Section: Discussionmentioning
confidence: 99%